2019
DOI: 10.3389/fendo.2019.00441
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Attenuates Renal Tubulointerstitial Fibrosis Associated With Type 1 Diabetes by Regulating STAT1/TGFβ1 Signaling

Abstract: Tubulointerstitial fibrosis (TIF) plays an important role in the progression of renal fibrosis in diabetic nephropathy (DN). Accumulating evidence supports a crucial inhibitory effect of dapagliflozin, a SGLT2 inhibitor, on TIF, but the underlying mechanisms remain largely unknown. This study aimed to shed light on the efficacy of dapagliflozin in reducing TIF as well as its possible impact on renal function. TIF in human kidney biopsies obtained from patients with DN was quantified by histopathological staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 33 publications
0
41
1
Order By: Relevance
“…For example, dapagliflozin promoted antifibrotic effects in a type 1 diabetic kidney disease model by ameliorating O-GlcNAcylation and reducing tubular hypoxia,[25] while others have found a downregulation in the Stat1/TGF-β pathway as well as decreased epithelial-to-mesenchymal transition. [26] Importantly, beneficial effects of SGLT2 inhibition were also demonstrated in non-diabetic kidney disease such as hypertensive nephropathy and were attributed to anti-inflammatory effects. [27] Similarly, anti-fibrotic effects of SGLT2 inhibition were found in liver[9] and heart,[10] where administration of dapagliflozin reduced cardiac fibrosis by stimulating M2 macrophages and inhibiting myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dapagliflozin promoted antifibrotic effects in a type 1 diabetic kidney disease model by ameliorating O-GlcNAcylation and reducing tubular hypoxia,[25] while others have found a downregulation in the Stat1/TGF-β pathway as well as decreased epithelial-to-mesenchymal transition. [26] Importantly, beneficial effects of SGLT2 inhibition were also demonstrated in non-diabetic kidney disease such as hypertensive nephropathy and were attributed to anti-inflammatory effects. [27] Similarly, anti-fibrotic effects of SGLT2 inhibition were found in liver[9] and heart,[10] where administration of dapagliflozin reduced cardiac fibrosis by stimulating M2 macrophages and inhibiting myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are in keeping with evidence from other organs where SGLT2 inhibition has been associated with antifibrotic effects, most prominently in the kidney but also in the heart and the liver. For example, dapagliflozin promoted antifibrotic effects in a type 1 diabetic kidney disease model by ameliorating O-GlcNAcylation and reducing tubular hypoxia,[25] while others have found a downregulation in the Stat1/TGF-β pathway as well as decreased epithelial-to-mesenchymal transition [26]. Importantly, beneficial effects of SGLT2 15/23…”
mentioning
confidence: 99%
“…These changes are in keeping with evidence from other organs where SGLT2 inhibition has been associated with antifibrotic effects, most prominently in the kidney but also in the heart and the liver. For example, dapagliflozin promoted antifibrotic effects in a type 1 diabetic kidney disease model by ameliorating O -GlcNAcylation and reducing tubular hypoxia [ 25 ], while others found a downregulation in the Stat1/TGF-β pathway, as well as decreased epithelial-to-mesenchymal transition [ 26 ]. Importantly, beneficial effects of SGLT2 inhibition were also demonstrated in nondiabetic kidney disease such as hypertensive nephropathy and were attributed to anti-inflammatory effects [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each pathway is regulated by a stimulus and other downstream regulators. Previous studies have suggested that myofibroblast activation acts as a major contributor to the renal fibrosis as they are the major producer of ECM proteins 25,26 .…”
Section: Discussionmentioning
confidence: 99%